Prevalence and Predictors of Violence Victimization and Violent Behavior among Youths: A Population-Based Study in Serbia - Obradovic-Tomasevic, Biljana (Int J Environ Res Public Health, 2019)
The study identifies the prevalence of violence victimization and the perpetration among youths, and explores the determinants and predictors using a socio-ecological model. The data of 36 variables from a representative sample of 1722 persons, ages 15–24 years, from the National Health Survey of Serbia in 2013, were analyzed by a multivariate logistic regression modeling. The study shows that 13.4% of youths experienced multi-victimization, while 10.4% were perpetrators of violence. Up to one-third of the victims were violence perpetrators. A small percentage of victims seek family and community support. Predictors of violence among youths were: male sex, households with fewer members, urban settlements, violence perpetration, self-assessed health as poor, lack of close friends and perception that it was difficult to obtain the assistance needed. Predictors of youth violence highlighted the need to improve health education, social support and community regulations, as well as strengthen the promotion of gender equality and a healthy environment.